Other desert cities : by Jon Robin Baitz. - Frith, Robert; Baitz, Jon Robin, 1961-; Black Swan State Theatre Company; Queensland Theatre Company ([Perth] : Black Swan State Theatre Company, 2013)
Poster advertising Black Swan State Theatre Company & Queensland Theatre Company's production of Jon Robin Baitz's "Other desert cities," State Theatre Centre of WA, 20 July-4 August, 2013. Features peach tinted portrait of actress Rebecca Davis; superimposed over her shirt is an image of a star field and, below, an upside down image of a building and plants. "In the best families, the secrets are buried the deepest" appears in the top left corner of the image; a quote from the Daily News appears to the right of Davis. The main image is surrounded by a background image of a desert settlement, with a hexagon pattern over the top half. ""Black Swan State Theatre Company and Queensland Theatre Company present" appears at the head of the poster; the Queensland Theatre Company and Black Swan State Theatre Company logos each appear in the bottom right. "City of Perth winter arts season" appears in the bottom right of the main image. Logos at foot of poster: Australian Government; Australia Council for the Arts; Government of Western Australia, Department of Culture and the Arts; Lotterywest; radio partner 720 ABC Perth; print media partner The West Australian; cast partner Worley Parsons Resources & Energy; associate partner City of Perth; principal partner Rio Tinto.
Caption title.
"Cover photo Robert Frith"--page 26, program, viewed online 20 February 2014 (http://www.bsstc.com.au/assets/Uploads/Files/Programmes/ODC-ProgramWEB.pdf).
National Library of Australia's copy previously folded, shows vertical and horizontal fold marks.
Keywords: Davis, Rebecca; Black Swan Theatre Company -- Posters; Theater -- Western Australia -- Posters; Theatrical posters -- Western Australia; Posters, Australian; Australia -- Posters; Australian